2013
DOI: 10.1002/adfm.201301250
|View full text |Cite
|
Sign up to set email alerts
|

Light Enhanced Electron Transduction and Amplified Sensing at a Nanostructure Modified Semiconductor Interface

Abstract: Visible and UV light are demonstrated to significantly enhance the sensing properties of an n‐type porous silicon (PS) extrinsic semiconductor interface to which TiO2 and titanium oxynitride (TiO2‐xNx) photocatalytic nanostructures are fractionally deposited. The acid/base chemistry of NH3, a moderately strong base, and NO2, a moderately strong acid, couples to the majority charge carriers of the doped semiconductor as the strong acid (TiO2) enhances the extraction of electrons from NH3, and the more basic TiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…In contrast, the response to NH 3 increased in the TiO 2− x N x modified PSi sensor for both UV and white light. When detecting NO 2 , Laminack and Gole had the opposite situation. The light had a marked effect on the resistance response to NO 2 for untreated PSi, which was counter to that observed for the PSi microstructure platform deposited with distinct nanostructured island sites of TiO 2 and TiO 2− x N x .…”
Section: Approaches To Optimization Of Psi‐based Gas and Vapor Sensorsmentioning
confidence: 96%
See 2 more Smart Citations
“…In contrast, the response to NH 3 increased in the TiO 2− x N x modified PSi sensor for both UV and white light. When detecting NO 2 , Laminack and Gole had the opposite situation. The light had a marked effect on the resistance response to NO 2 for untreated PSi, which was counter to that observed for the PSi microstructure platform deposited with distinct nanostructured island sites of TiO 2 and TiO 2− x N x .…”
Section: Approaches To Optimization Of Psi‐based Gas and Vapor Sensorsmentioning
confidence: 96%
“…To measure the change in response to NO 2 , a UV lamp was introduced in the enclosed testing chamber. Laminack and Gole also studied the influence of light on the sensor response of PSi‐based sensors. They found that white light and UV light did not have any effect on the sensor response to NH 3 for untreated PSi.…”
Section: Approaches To Optimization Of Psi‐based Gas and Vapor Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of low light levels (≤ ! Watt) demonstrates the feasibility for developing Solar Pumped Sensors [13]. The ability to deal with water vapor contamination has been demonstrated [14].…”
Section: The Interfacementioning
confidence: 99%
“…In addition, the sensor platforms are capable of operation under extremely small magnetic field control [27]. The devices have the potential for adaptation to solar pumped sensing, micro-reactor, and solar assisted micro-reactors to achieve difficult but important chemical transformations, extending the development of basic heterogeneous catalyst sites and potential acid/base pairing combinations [28]. The technology has now been applied to the characterization of volatile liquids including the alcohols, acetone, chloroform, additional polar and nonpolar solvents, and more complex liquids including isoprene.…”
Section: Technology Featuresmentioning
confidence: 99%